COOPERATIVE DEVELOPMENT MODEL "MERAH PUTIH" BASED ON SHARIA ECONOMICS TO IMPROVE THE WELFARE OF VILLAGE COMMUNITIES - Muhamad Izazi Nurjaman; Sisi Ade Linda; Camelia Sofwan Al-Rasyid; Keuis Hera Susanti; Nita Eldiani (Gunung Djati Conference Series, 2025)
This study aims to examine and formulate a development model for the Merah Putih Cooperative based on sharia economics that is effective in improving the welfare of rural communities. In the context of increasing economic inequality and weak access for rural communities to fair and inclusive financial institutions, cooperatives based on sharia values ​​are a strategic alternative in realizing economic justice and empowering local communities. The research method used is library research with a qualitative approach. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of the study indicate that the development of the Merah Putih Cooperative needs to be directed at sharia principles such as justice, deliberation, profit sharing, and the prohibition of usury, and strengthened by member education, collaboration between communities, and support from state policies. This model is not only able to strengthen the resilience of the village economy through the real sector and MSMEs, but also form a more independent, inclusive, and sustainable local economic order in accordance with Islamic values.